Near-Infrared Aggregation-Induced Emission-Active Probe Enables in situ and Long-Term Tracking of Endogenous β-Galactosidase Activity - Fu, Wei; Yan, Chenxu; Zhang, Yutao; Ma, Yiyu; Guo, Zhiqian; Zhu, Wei-Hong (Frontiers in Chemistry, 2019)
High-fidelity tracking of specific enzyme activities is critical for the early diagnosis of diseases such as cancers. However, most of the available fluorescent probes are difficult to obtain in situ information because of tending to facile diffusion or inevitably suffering from aggregation-caused quenching (ACQ) effect. In this work, we developed an elaborated near-infrared (NIR) aggregation-induced emission (AIE)-active fluorescent probe, which is composed of a hydrophobic 2-(2-hydroxyphenyl) benzothiazole (HBT) moiety for extending into the NIR wavelength, and a hydrophilic β-galactosidase (β-gal) triggered unit for improving miscibility and guaranteeing its non-emission in aqueous media. This probe is virtually activated by β-gal, and then specific enzymatic turnover would liberate hydrophobic AIE luminogen (AIEgen) QM-HBT-OH. Simultaneously, brightness NIR fluorescent nanoaggregates are in situ generated as a result of the AIE-active process, making on-site the detection of endogenous β-gal activity in living cells. By virtue of the NIR AIE-active performance of enzyme-catalyzed nanoaggregates, QM-HBT-βgal is capable of affording a localizable fluorescence signal and long-term tracking of endogenous β-gal activity. All results demonstrate that the probe QM-HBT-βgal has potential to be a powerful molecular tool to evaluate the biological activity of β-gal, attaining high-fidelity information in preclinical applications.